Some Population Parameters of Capoeta umbla (Heckel, 1843) Living in Ozluce Dam Lake, Turkey - Eroglu, Mucahit; Dusukcan, Mustafa; Coban, Mehmet Zulfu (Kahramanmaras Sutcu Imam Univ, 2018)
This study was conducted bet Nveen October 2015 and March 2016 in Ozluce Dam Lake located bet ween Elazig and BingOl. A total of 376 (153 male, 223 female) Camera umbla (Heckel, 1843) samples were examined in the study and it was (let ermined that the samples were distributed among the I-XII age groups and female/male ratio was determined as 11.46. Total lengths were determined as 15.90-39.70 cm in males and 18.10-46.70 cm in females. Total weights were measured as 35.0-592.9 g for males and 48.0-1190.0 g for females; the condition factors were computed as 0.672-1.544 for males and 0.541-1.494 for females. Length-weight relationship equations were estimated as W= 0.0066*TL3.0928 (R-2=0.95) for males. W= 0.0072*TL3.0644(R-2=0.89) for females and W= 0.0071*TL3.0702(R-2=0.94) for all population. The von Bertalanffy growth equation (VBCE) parameters were calculated as L infinity =47.12 cm, K=0.12, t(0) =-2.78, W infinity =987.26 g for males, L infinity =50.59 cm, K=0.14, t(0) =-1.99, W infinity =1200.24 g for females and L infinity =49.83 cm, K=0.13, t(0) =-2.13, W infinity = 1155.83 g for all population.
Keywords: Capoeta umbla; Growth properties; Ozluce Dam; Age